2017
DOI: 10.1159/000479398
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Eryptosis, the Suicidal Erythrocyte Death by Mammalian Target of Rapamycin (mTOR) inhibitor Temsirolimus

Abstract: Background/Aims: The mammalian target of rapamycin (mTOR) inhibitor temsirolimus is utilized for the treatment of malignancy. Temsirolimus is at least in part effective by triggering suicidal tumor cell death. The most common side effect of temsirolimus treatment is anemia. At least in theory, the anemia following temsirolimus treatment could result from stimulation of eryptosis, the suicidal erythrocyte death. Hallmarks of eryptosis include cell shrinkage and cell membrane scrambling with phosphatidylserine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 163 publications
0
4
0
2
Order By: Relevance
“…Temsirolimus triggers apoptosis in tumor cells via activation of caspases. 32 This drug causes the suspension of protein synthesis that manages the proliferation, growth, and survival of tumor cells. Cells exposed to temsirolimus encounter a cell cycle arrest in the G1 phase, and it also decreases the production of vascular endothelial growth factor (VEGF) resulting in the inhibition of tumor angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temsirolimus triggers apoptosis in tumor cells via activation of caspases. 32 This drug causes the suspension of protein synthesis that manages the proliferation, growth, and survival of tumor cells. Cells exposed to temsirolimus encounter a cell cycle arrest in the G1 phase, and it also decreases the production of vascular endothelial growth factor (VEGF) resulting in the inhibition of tumor angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Temsirolimus triggers apoptosis in tumor cells via activation of caspases . This drug causes the suspension of protein synthesis that manages the proliferation, growth, and survival of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, co-treatment of cells with RA and STSP (Figure 7) resulted in significantly less hemolysis than that observed in cells treated with RA alone. Previous reports have unequivocally demonstrated that PKC mediates RBC death induced by excessive Ca 2+ entry [36] and by eryptosis inducers costunolide [37] and temsirolimus [38], among others. Collectively, these studies indicate that PKC acts downstream of Ca 2+ accumulation but upstream of reactive oxygen species generation.…”
Section: Discussionmentioning
confidence: 97%
“…Это делает слой менее текучим по сравнению с теми, которые находятся в составе фосфатидилэтаноламина и фосфатидилсерина внутренней поверхности. Во-вторых, отрицательно заряженный фосфатидилсерин, взаимодействующий с регуляторными и структурными белками, при нарушении асимметрии приводит к экспонированию фосфатидилсерина на наружной поверхности, что является сигналом к эриптозу [49,50,82,254], а также к изменению соотношения зарядов на внутренней и внешней сторонах бислоя мембраны эритроцита. Таким образом, aссимметрия фосфолипидов определяет текучесть мембраны (fragility) и вносит важный вклад в поддержание механических свойств мембраны [95,236].…”
Section: ãëèêîôîðèíunclassified
“…Многочисленными исследованиями установлено, что эриптоз запускается прежде всего повышением внутриклеточной концентрации свободных ионов кальция, а также рядом веществ эндогенного и экзо генного происхождения: металлами и их соединениями, лекарственными препаратами и ксенобиотиками [26,27,51,90,91,267,268]. Воздействие этих веществ либо запускает механизмы, связанные с повышением внутриклеточной концентрации свободных ионов кальция и усилением выработки эндогенного церамида, либо активирует дополнительные механизмы, такие как энергетическое истощение по АТФ, окислительный стресс и/или активация каспазы 3.…”
Section: молекулярные механизмы процесса эриптозаunclassified